2014
DOI: 10.1111/anae.12904
|View full text |Cite
|
Sign up to set email alerts
|

The impact of autonomic dysfunction on peri‐operative cardiovascular complications

Abstract: SummaryCardiovascular autonomic neuropathy is frequently observed in patients with diabetes mellitus. As anaesthesia has a marked effect on peri-operative autonomic function, the interplay between diabetic neuropathy and anaesthesia may result in unexpected haemodynamic instability during surgery. The objective of this literature review was to examine the association of cardiovascular autonomic neuropathy with peri-operative cardiovascular complications. We searched PubMed for articles with search elements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
0
18
1
4
Order By: Relevance
“…In particular, it was more apparent in the uncontrolled diabetic patients with reduced heart rate. [14] On the other hand, decrease in the cerebral saturation and heart rate in our study has not been previously reported in other cardiac surgery studies, which is an interesting aspect of the current study. Manipulation of nodal areas, which controls the heart rate in the right atrium during cannulation, may cause arrhythmia and heart rate alterations.…”
Section: Discussioncontrasting
confidence: 51%
“…In particular, it was more apparent in the uncontrolled diabetic patients with reduced heart rate. [14] On the other hand, decrease in the cerebral saturation and heart rate in our study has not been previously reported in other cardiac surgery studies, which is an interesting aspect of the current study. Manipulation of nodal areas, which controls the heart rate in the right atrium during cannulation, may cause arrhythmia and heart rate alterations.…”
Section: Discussioncontrasting
confidence: 51%
“…[19] The inability of the ANS to activate effective circulatory reflexes to maintain hemodynamic stability is a feature of LCOS. While it is well-recognized that cardiovascular autonomic neuropathy in diabetic patients may result in unexpected hemodynamic instability during surgery, [20] very few studies have analyzed the impact of autonomic dysfunction on post/peri-operative outcomes in a general population or in cardiac surgery patients. [21, 22]…”
Section: Introductionmentioning
confidence: 99%
“…Kardiyopulmoner arrest, hatta ölüm görülebilmektedir. Dolayısıyla KON bulgusu olan tüm hastaların postoperatif kardiyak komplikasyonlar açısından yakın takibi gerekmektedir 42 .…”
Section: Postoperatif Dönemunclassified